Pelibatan Komisi Pemberantasan Korupsi dalam Pengawasan Hakim Mahkamah Agung dalam Lingkungan Peradilan Perspektif Fath Dhari’ah - Hofifah Hofifah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
The question is still often asked whether the Corruption Eradication Commission (KPK), in carrying out its function as the vanguard of corruption eradication (TIPIKOR), also supervises judges within the Supreme Court (MA) judiciary. Even though from a juridical perspective, the KPK's authority is not included in the supervision of individual Supreme Court judges who have become the authority of the Judicial Commission (KY), the KPK continues to supervise issues of corruption, gratuities, buying and selling of cases and other forms of TIPIKOR within the Supreme Court justice environment, and not judges as the object. This research envisages what if the KPK is involved in supervising Supreme Court judges by using the thinking method of Fath Dhari'ah, which considers the good and bad consequences of establishing law. This study uses a normative method with descriptive analysis techniques. The result of this study is that the involvement of the KPK in supervising Supreme Court judges in the Supreme Court justice environment contains more mafsada than the desired maslahah.